(untitled) (Research, Society and Development, 2020)
Introduction: This is a study about the difficulty faced in primary care units to implement permanent education as a political-pedagogical process for qualifying care. Permanent education activities should be used as a tool to bring professional practice closer to the reality of each population. We aim to identify in the literature, how permanent education has been incorporated into the daily routine of primary care units; and to encourage discussions about the importance of permanent education for qualifying the care provided by Primary Care. Method: An Integrative Literature Review was carried out, according to the PICO strategy (participants, intervention, context, results), whose data collection was carried out in June 2019, in the Latin American and Caribbean Science Literature databases (LILACS), Web of science, SciVerse Scopus, PUBMED and Nursing Databases (BDENF). Results: From the 12 articles selected for analysis in the study, it was possible to define three relevant topics for discussion: “Permanent Education in the routine of primary care”, “Permanent Education and the qualification of care in Primary Care” and “The knots conceptual frameworks for the implementation of EPS”. Conclusion: The theme of permanent health education, being increasingly recognized as a fundamental tool for conducting, reorganizing and qualifying work processes in primary care. However, one bias that we can cite is the lack of clarity and understanding regarding the concepts that involve EPS and how much it impacts the effectiveness of EPS as a health policy.